Pendampingan Aplikasi Personal Health Record Berbasis AI untuk Deteksi Dini dan Monitoring Penyakit Kronis bagi Warga Desa Kalongan Kabupaten Semarang - Widianawati, Evina; Pantiawati, Ika; Wulan, Widya Ratna; Kusuma, Edi Jaya (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to improve the knowledge, attitudes, and behaviors of residents in Kalongan Village, Semarang Regency, for early detection and monitoring of chronic diseases through the use of an Artificial Intelligence (AI)-based Personal Health Record (PHR) application. The implementation method of this service included Survey, Socialization and Mentoring the practice of using the PHR-AI application. The evaluation instrument used a questionnaire and the data was analyzed descriptively in percentage growth. The results of this activity showed active participation from all attendees in discussions and socialization sessions on chronic diseases, PHBS, and the PHR-AI application for chronic disease detection. There was a significant improvement in participants’ knowledge, attitudes, and behaviors, indicating that the socialization of the PHR-AI application was highly beneficial in raising awareness about chronic disease risk factors. Participants were able to understand and practice the material presented during the sessions, which involved a combination of presentations, hands-on practice, and discussions. Additionally, participants actively consulted with facilitators during health screenings and enthusiastically joined the exercise sessions to maintain their health.